»Failed« Migratory Adventures? Malian Men Facing Conditions Post Deportation in Southern Mali - Schultz, Susanne U. (Theater, 2022)
The effects of the intra-African and European deportation regimes brought about since the European Union's externalization of its migration and development policy by transferring it to countries of sub-Saharan Africa remain largely understudied - especially their effects on people's everyday life after forced returns. Based on extensive field research, Susanne U. Schultz's book analyses the supposedly "failed" migration of Malian men, the social situations in which they find themselves following deportation, and the implications of their "failure" for their social environment and broader society. This important ethnographic study creates empirical knowledge on key issues in migration research, policy, and practice in the context of a charged debate.